ZnO and ZnO/CaO nanoparticles in alginate films. Synthesis, mechanical characterization, barrier properties and release kinetics. (September 2019) - Aristizabal-Gil, María V.; Santiago-Toro, Sebastián; Sanchez, Leidy T.; Pinzon, Magda I.; Gutierrez, Jorge A.; Villa, Cristian C.
Abstract: The aim of this paper was the synthesis of a nano-composed sodium alginate edible film containing ZnO and ZnO/CaO NPs and their mechanical, barrier and optical properties as well as the mechanism and release kinetics of the nanoparticles into food simulants were studied. ZnO NPs have a strong interaction with alginate molecules, reducing water vapour permeability and affecting their mechanical properties. On the other hand, ZnO/CaO NPs form aggregates that disrupt the polymeric structure of the alginate films increasing vapour permeability from 3.5 7.2 ± 0.3 g/Pa ∗ s ∗ m to 4.1 ± 0.1 g/Pa ∗ s ∗ m, and reducing the film's opacity from 14.2 ± 0.1 to 10.6 ± 0.2 Abs/mm. Also, the Ca and Zn release from the films into several food simulant media was studied, showing a Fickian type behaviour whit Peppas release coefficients (n) around 0.50 and faster release rates in lipophilic media, and that release kinetics are strongly dependent of the NPs concentration in the films. In conclusion, alginate edible films containing ZnO and ZnO/CaO can be used as active agents in the development of active food packaging. Highlights: Edible films from alginate containing ZnO and ZnO/CaO nanoparticles were made. ZnO/CaO nanoparticles inclusion allows more transparent and less permeable films. Nanoparticles release from the composite films is favored in non-polar solvents.